Colonization and usage of an artificial urban wetland complex by freshwater turtles - Marc Dupuis-Desormeaux; Christina Davy; Amy Lathrop; Emma Followes; Andrew Ramesbottom; Andrea Chreston; Suzanne E. MacDonald (PeerJ, 2018)
Conservation authorities invest heavily in the restoration and/or creation of wetlands to counteract the destruction of habitat caused by urbanization. Monitoring the colonization of these new wetlands is critical to an adaptive management process. We conducted a turtle mark-recapture survey in a 250 ha artificially created wetland complex in a large North American city (Toronto, Ontario). We found that two of Ontario’s eight native turtle species (Snapping turtle (SN), Chelydra serpentina, and Midland Painted (MP) turtle, Chrysemys picta marginata) were abundant and both were confirmed nesting. The Blanding’s turtle (Emydoidea blandingii) was present but not well established. Species richness and turtle density were not equally distributed throughout the wetland complex. We noted SN almost exclusively populated one water body, while other areas of the wetland had a varying representation of both species. The sex ratios of both SN and MP turtles were 1:1. We tracked the movement of Snapping and Blanding’s turtles and found that most turtles explored at least two water bodies in the park, that females explored more water bodies than males, and that 95% of turtles showed fidelity to individual overwintering wetlands. We performed DNA analysis of two Blanding’s turtles found in the created wetlands and could not assign these turtles to any known profiled populations. The genetic data suggest that the turtles probably belong to a remnant local population. We discuss the implications of our results for connectivity of artificial wetlands and the importance of the whole wetland complex to this turtle assemblage.